Do tobacco taxes influence starting and quitting smoking? A duration analysis approach using evidence from a sample of Irish women - David Madden (University College Dublin, Department of Economics, 2002)
This paper uses duration analysis to investigate factors influencing starting and quitting smoking, in particular the role of tobacco taxes. Applying a variety of parametric duration models, including a split population model, to a sample of Irish women, it finds mixed results regarding the effect of tobacco taxes. In general the coefficient on tobacco taxes is in the expected direction but in some cases statistical significance is low. The paper finds among other factors education, health knowledge and marital status to be most important with very little role for advertising bans.
hdl:10197/762
Keywords: I18; D12; C41; 330; Duration; Split Population; Smoking; Tabaksteuer; Rauchen; Frauen; Irland; Statistische Bestandsanalyse